1989
DOI: 10.1177/002194368902600401
|View full text |Cite
|
Sign up to set email alerts
|

Listening, Communication Abilities, and Success at Work

Abstract: Although many have argued that listening is particularly important in organizations, few studies have examined listening and listening skills in this context. This study examined relationships between listening, communication related abilities, employee level in an insurance company, and upward mobility. The results indicated significant positive relationships between listening and other social cognitive and communicative abilities. While findings suggested that nonsupervisors tended to possess better listenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Higher job position, which in our study also seemed to predict improved performance in processing information provided by the speaker, has been associated with memory cognitive skills as well (Avolio and Waldman 1994). Moreover those holding higher level positions have been found to exhibit better communication and listening abilities (Davenport Sypher et al 1989). Where Greece is concerned, all teachers-principals or not-attend the same undergraduate studies.…”
Section: Processing Subscalesupporting
confidence: 54%
See 1 more Smart Citation
“…Higher job position, which in our study also seemed to predict improved performance in processing information provided by the speaker, has been associated with memory cognitive skills as well (Avolio and Waldman 1994). Moreover those holding higher level positions have been found to exhibit better communication and listening abilities (Davenport Sypher et al 1989). Where Greece is concerned, all teachers-principals or not-attend the same undergraduate studies.…”
Section: Processing Subscalesupporting
confidence: 54%
“…Again, as discussed above, such training incorporates communicative skills (Kaminski et al 2008;Puura et al 2002;Ragozzino et al 2003) and includes modeling and roleplaying of relative useful techniques and strategies (Han and Weiss 2005). Job position was also identified as a predictor for better active listening performance through the Listening skill subscale, confirming the finding that those occupying higher level positions possess better communication abilities (Davenport Sypher et al 1989). Having students in need of special education appeared associated with better performance in Listening skill as well; it seems that the teachers who deal with such students possibly tend to develop more empathy and better listening skills in order to be able to understand them better.…”
Section: Listening Skill Subscalementioning
confidence: 69%
“…Model 2 demonstrates that LS has a moderate effect (r =.341) on CS. This finding coincides with the results of some studies in the literature (Davenport Sypher et al, 1989;Şimşek, 2019). In their study, Davenport Sypher et al (1989) found that various aspects of listening (selective listening, short-term listening, short-term listening with rehearsal, lecture listening, interpretive listening) and each of the skills related to communication (cognitive differantiation, persuasive arguments, self-monitoring, perspective-taking) revealed medium and high positive correlations.…”
Section: The Relationship Between Ls Ess and Cssupporting
confidence: 92%
“…So for employees, the expectation is that they must listen to learn. A study found that nonsupervisory employees tended to possess better listening abilities than supervisors (Sypher et al, 1989).While another study revealed that when the employees were not listening to their managers, they would act as if they were (Hunsaker & Alessandra, 1980). The plot for the estimated marginal means for managers and nonmanagers on country of residence is shown in Figure 1 in the appendix.…”
Section: The Distracted Listenermentioning
confidence: 99%